SEED PRODUCTION OF THE MATERNAL FORMS OF BEE POLLINATED CUCUMBER HYBRIDS USING GIBBERELLIN - I. B. Korottseva; L. A. Kochetkova (Овощи России, 2015)
The data of using of gibberellin for seed production in maternal forms of bee pollinated cucumber F1 hybrids, Black F1, and Frant F1 are shown.